Oral health and the presence of infectious microorganisms in hospitalized patients : a preliminary observational study - Cruz, Adriana Silva da Costa (2022)
Objective: Characterise oral health, and the presence in the oral cavity of pathogenic non-oral microorganisms potentially associated with nosocomial infections and antimicrobial resistance in non-intubated patients admitted to a Brazilian university hospital. Materials and methods: An intraoral examination and oral swab were performed on hospitalized individuals at three different times, T1 (within 48 h of hospitalization), T2 (48 h after T1) and T3 (7 days after hospitalization). The oral health status was defined by the Oral Health Assessment Tool (OHAT) and Tongue Coating Status (TCS). The swabs were processed and microorganisms potentially related to nosocomial infections were phenotypically identified through colony morphology, staining and microscopy. Results: The most prevalent microorganisms were Escherichia coli, Enterococcus spp., Enterobacter spp., Pseudomonas spp., Candida albicans and Staphylococcus aureus. The oral health status was considered median, and the tongue coating index was considered high throughout the study period. The prevalence of potentially pathogenic non-oral microorganisms was high and constant from the first 48 h to the seventh day of hospitalization. Conclusions: The results point out that the mouth can act as a reservoir of epidemiologically important pathogens within hospital settings, even in patients without mechanical ventilation, thus increasing the risk of nosocomial infections in susceptible individuals.